2012
DOI: 10.1002/ctpp.201100063
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Polarization Around Dust Particle in an External Electric Field

Abstract: The effect of plasma polarization around a negatively charged dust particle is investigated with the help of Monte Carlo simulation of ion trajectories in the electric field of the dust particle and an external electric field. The induced dipole moment of such a system was estimated in a wide range of dust particle and plasma parameters. It is shown that the dipole moment is very large, and has a non-monotonous dependence on the external electric field. For a small external electric field, it weakly depends on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…The considered range of the plasma parameters is Γ = 20–160, and k S = 1.0−2.0. In general, Γ d is not independent of Γ. Sukhinin et al , showed that the ion cloud focused as a result of the external electric field and attraction by the charged dust particle can have a volume charge ∼ Q /2 placed at a distance ∼ λ S /2 from the dust particle. Therefore, we consider Γ d in the range 0–Γ d (= 0.2 × Γ).…”
Section: Introductionmentioning
confidence: 99%
“…The considered range of the plasma parameters is Γ = 20–160, and k S = 1.0−2.0. In general, Γ d is not independent of Γ. Sukhinin et al , showed that the ion cloud focused as a result of the external electric field and attraction by the charged dust particle can have a volume charge ∼ Q /2 placed at a distance ∼ λ S /2 from the dust particle. Therefore, we consider Γ d in the range 0–Γ d (= 0.2 × Γ).…”
Section: Introductionmentioning
confidence: 99%
“…In the weakly collisional conditions Q ∞ comes to zero, η ≈ 0.5, and second term consists with the result of the kinetic approach [4]. In the paper of Sukhinin et al [8] the total dipole moment inside calculation region was calculated by the molecular dynamic for the mean free path length of ions l i = 10λ D and l i = 2λ D . The last case can be compared with the present results taking into account finite size of the calculation region.…”
mentioning
confidence: 99%
“…Taking into account (8) and (10) we have Figure 2. The dependence of the reduced dipole moment on a size of the integration layer for E ′ = 1 (a) and on the reduced external electric field for L = 10λ D (b); line is hydrodynamic approach, triangles and squares are molecular dynamic results [8].…”
mentioning
confidence: 99%
See 2 more Smart Citations